Pharmacognostical Properties and their Traditional Uses of Cassia tora Linn. - Shakywar, Yogesh (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Cassia tora Linn. (Caesalpiniaceae) is a small annual herbs or under shrub growing as common weed in Asian countries in rainy season, the herbs 1.2 m in height. It is well know anthraquinone containing plant, constitutes of Ayurvedic preparation in India. In present review has been made emphasis on it traditional uses and properties and uses in management of various diseases in India and china. Key words: Cassia tora, medicinal uses, pharmacognostical properties, chemical constituent.